Heat stress tolerance determines the survival and growth of introduced Canadian sugar maple in subtropical China. (19th September 2018) - Zhu, Yingying; Fu, Songling; Liu, Hua; Wang, Zhaocheng; Chen, Han Y H
Abstract: The introduction of species contributes to both ecological restoration and regional economics, while serving as a potential strategy to conserve species under rapid climate change. Despite an anticipated significant increase in temperature at high latitudes by the end of the 21st century, very few experimental migration trials have been conducted regarding large climate range changes. We employed a provenance trial by introducing a temperate sugar maple ( Acer saccharum Marsh) of three provenances with a mean annual temperature of 3.0 °C in Manitoba, 4.2 °C in Quebec and 9.4 °C in Ontario, Canada, to 15.8 °C at an introduced site in subtropical China. We measured survival, growth, summer photosynthesis in the field and stress-resistance responses under a temperature gradient in growth chambers with first-year seedlings. We found that the Ontario provenance had the highest propensity for survival and growth, followed by the Quebec provenance, while the Manitoba provenance had the lowest. The photosynthetic parameters of the seedlings changed over time of the day, with the Ontario provenance having a higher photosynthesis rate and stomatal conductance than the Quebec and Manitoba provenances. Furthermore, the growth chamber results revealed that the Ontario provenance had the best physiological adjustment for self-protection from heat stress, followed by the Quebec and Manitoba provenances. Our results suggested that the change in climate range drove the survival and growth of introduced seedlings and that the tolerance to summer heat stress through physiological mechanisms was responsible for the success of species introduction, from a cold to a warm climate.